Functional food product development - Smith, Jim, 1953-; Charter, Edward (Chichester, West Sussex : Wiley-Blackwell, 2010)
'The market for functional food products is estimated at between US$10 billion and US$30 billion and is expected to double by 2010. With this demand for new products comes a demand for product development and supporting literature for that purpose. This book provides a much-needed review of important opportunities for new products from many perspectives including from those with in-depth knowledge of as-yet unfulfilled health-related needs. The book addresses functional food product development from a number of perspectives: the process itself; idea creation; regulation; health research that may provide opportunities; and processes and ingredients. It also features case studies that illustrate real product development and commercialization histories. Written for food scientists and technologists, the book presents practical information for use in functional food product development. It is intended for use by practitioners in functional food companies and food technology centres and will also be of interest to researchers and students of food science'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Functional foods; Food industry and trade; Food Technology -- methods; Food -- Standards; Food-Processing Industry -- methods; Nutritional Physiological Phenomena